ANALISIS PENDAPATAN USAHA TANI PADI SAWAH (Oryza Sativa) DI DESA LEGU WODA KECAMATAN MAGEPANDA KABUPATEN SIKKA - Iawan Saputera Wanda, Taras; Liga, Floribertus; Noni, Sarlina (Universitas Cokroaminoto Palopo, 2025)
This research aimed to analyze the income of rice farming in Legu Woda Village, Magepanda Sub-District, Sikka Regency and determine its feasibility through the calculation of the R/C ratio and Break Even Point (BEP). The research method used was descriptive quantitative, with primary data collected through interviews using questionnaires involving 68 rice farmer respondents. The results showed that the average rice production was 3.668 kg/ha with a selling price of IDR 7.000/kg. Farmers’ income reached IDR 19.737.177/ha per planting season with a total cost of IDR 5.938.823/ha. The R/C ratio value was 4.32 (>1), indicating that rice farming in the research area was efficient, profitable, and feasible to cultivate, BEP analysis showed the break-even point at a production level of 337,06 kg/ha, revenue of IDR 2.358.062,57/ha, and a grain price of IDR 1.619,09/kg. This shows that rice farming in Legu Woda Village is worth pursuing because it provides significant profits.